The Saving and Investing Behaviors of Members of Large Credit Cooperatives in General Santos City: Their Risk Attitude, the Cooperative’s Investment Schemes, and Corporate Earnings - Dugasan, Princess Justine M.; Cruz, Marissa G. Dela (International Journal of Research in Interdisciplinary Studies, 2025)
This study examined the saving and investing behaviors of members of large credit cooperatives in General Santos City, focusing on the influence of members’ risk attitudes, cooperative investment schemes, and expected corporate earnings. The findings revealed that the majority of members possessed high educational attainment, stable full-time employment, and fell within the middle-income bracket, factors that contributed to financially prudent and consistent saving and investing habits. Members displayed a generally conservative approach to risk, favored low- to moderate-risk financial products, and demonstrated increased financial activity when cooperative earnings were perceived to be strong. Trust in the cooperative, particularly in its investment schemes and financial stability, emerged as a critical factor influencing both saving and investing decisions. Automatic savings mechanisms, incentives, and transparent financial reporting further reinforced positive financial behavior. Statistically significant relationships were found between members' financial behaviors and their risk attitudes, the cooperative's investment offerings, and expectations of corporate earnings. Additionally, socioeconomic factors—especially education and employment, played a vital role in shaping financial decision-making. The findings underscored the importance of trust, financial literacy, and well-structured investment options in fostering proactive and sustained financial engagement among cooperative members.